Research on the formation mechanism of information cocoon and individual differences among researchers based on information ecology theory - Yuan, Xiaofang; Wang, Chunyun (Frontiers in Psychology, 2022)
To analyze the formation mechanism of the information cocoon of researchers, the differences among different individuals, and to provide countermeasures to break its adverse effects. Based on information ecology theory, a theoretical model is constructed regarding information people, information, information environment, and information technology, and relevant data are collected through questionnaires to verify the hypotheses. It was found that the differences in gender, education, status, age, and team size of researchers lead to differences in their information cocoons. Community influence, information homogeneity, and value identity are essential factors forming researchers' information cocoons. Community influence and information homogeneity positively influence value identity. In future research, researchers should pay attention to information homogeneity, community influence, and value identity.